محمد أركون رؤية في مسارات الأنسنة - بولقواس, زرفة (Changement Social; No 4 (2018): revue change social, 2018)
تهدف هذه الورقة البحثية إلى فحص وتحليل موقف محمد أركون تجاه الأنسنة، والتي هي أساس الفكر التنويري، إذ بارع في التنقيب عن جذور المفهوم فلسفيا وبالأخص في حضارة العصر الذهبي الكلاسيكية خصوصا جيل التوحيدي ومسكويه. واختيار موضوع الأنسنة لمحمد أركون كان المهم فيه ليس موقفه في حد ذاته، وإنما كيف استدل على وجوده قبل القرن التاسع عشر في الفكر الغربي، ودلالات الافتخار بكونه أول من استعمل مصطلح الأنسنة في الفكر الإسلامي، رغم اعترافه بازدهار التيار الإنساني العقلاني في القرن الرابع الهجري . This studyaims to analyze Mohammed Arkoun's vision of humanity, whichis the basis of Enlightenmentthought. Sought to find the roots of the philosophical concept, especially in the classical golden Age civilization and precisely the atawhidy and Muskawihgeneration.The choice of Muhammad Arkoun'shumanismwas important not to his position, but how hewasconfirmedbefore the nineteenthcentury in Western thought, and signs of pride as the first to use the termhumanism in Islam thought, despite the recognition of the flourishinghumanrationalism in the fourthcentury AH The models of humanismwerediscussedatArkounwithoutexceedinghis vision of humanism and the difficulty of achievingit in reality, in addition to analyzing the most important dimensions of humanity, from the mentality to the historical.